Religious Education and religious literacy: a professional aspiration? - Conroy, James C. (British journal of religious education, 2016)
This paper draws on an AHRC/ESRC funded, three-year multi-dimensional study of the political, cultural and pedagogical practices of religious education (Project AH/F009135/1). More specifically, it draws on that material to help understand the challenges to a sense of professional identity amongst UK religious education teachers. The empirical findings are here located in and shed light on prior discussions of the extent to which teachers in general are to be considered professional. These prior discussions have seen the idea of teacher professionalism come under sustained attack with the conflation of the conceits of professional, vocation and occupation, and the opening section of the paper tries to understand how this has come to pass. This concern with professional identity is subsequently pursued into the domain of religious education and the ways in which, amongst other concerns, the rise of a deracinated examination process and the neglect of religious literacy have contributed significantly to the diminution of the religious education teacher as a professional.